Profil Lajnah Pentashihan Mushaf al Qur'an Badan Litbang dan Diklat Kementerian Agama RI - Profil... (Lajnah Pentashihan Mushaf al Qur'an Badan Litbang dan Diklat Kementerian Agama RI, 2013)
ng,1/nr,c.1/ws.c.2